ANIMAL RESEARCH IN THE JOURNAL OF APPLIED BEHAVIOR ANALYSIS - Edwards, Timothy L.; Poling, Alan (Journal of applied behavior analysis, 2011)
This review summarizes the 6 studies with nonhuman animal subjects that have appeared in the Journal of Applied Behavior Analysis and offers suggestions for future research in this area. Two of the reviewed articles described translational research in which pigeons were used to illustrate and examine behavioral phenomena of applied significance (say—do correspondence and fluency), 3 described interventions that changed animals' behavior (self‐injury by a baboon, feces throwing and spitting by a chimpanzee, and unsafe trailer entry by horses) in ways that benefited the animals and the people in charge of them, and 1 described the use of trained rats that performed a service to humans (land‐mine detection). We suggest that each of these general research areas merits further attention and that the Journal of Applied Behavior Analysis is an appropriate outlet for some of these publications.